Dynamic modeling and high-precision attitude slew maneuver with extended disturbance observer for flexible spacecraft - Zhang, Lei; Ren, Hui; Zhou, Ping; Fan, Wei (Nonlinear dynamics, 2025)
The maneuver accuracy of modern flexible spacecraft is significantly impacted by the vibration of flexible solar arrays. Traditionally, the vibration effect is usually represented by a few low-order modes and associated perturbations on the attitude are compensated by various methods. However, it is unclear whether the vibrations are accurately described and perturbations are adequately compensated. In this work, a novel low-order dynamic modeling method and high-precision control scheme are proposed for the attitude slew maneuver of spacecraft equipped with a pair of flexible solar panels. A model reduction method tailored for attitude control scenarios is presented to reduce the dimension of the dynamic model developed by the reference nodal coordinate formulation. Compared to the previous nonlinear model reduction methods, the present method results in a simpler formulation that can accurately describe the influence of flexible appendages on spacecraft attitude using only linear modes. The extended disturbance observer is employed to estimate the disturbances caused by the flexible panels and provide compensatory control to address the challenge of insufficient precision in bang-bang slew maneuvers for flexible spacecraft. Results demonstrate that the proposed low-order model reliably calculates bending deformations and accurately characterizes the influence of appendage flexibility on spacecraft attitude. Furthermore, the extended disturbance observer can significantly enhance the accuracy of bang-bang control for flexible spacecraft, thus that the effectiveness of the proposed control strategy is verified.